Hematoma subdural intracraniano: uma rara complicação após raquianestesia: relato de caso - Bisinotto, Flora Margarida Barra (2012)
BACKGROUND AND OBJECTIVES: Intracranial subdural hematoma is a rare complication following spinal anesthesia. The diagnosis is usually difficult because initial symptoms are the same of post-dural puncture headache. The objective was to report a case of early diagnosed subdural hematoma after spinal anesthesia performed with a fine-gauge needle and single puncture. CASE REPORT: 48-year old female patient, ASA I, undergoing spinal anesthesia for surgery to correct urinary incontinence. The spinal anesthesia was performed with 27G Quincke needle and single puncture. There was no unexpected event in the surgery and the patient was discharged. After 48 hours of spinal puncture, the patient reported sudden, strong headache, affecting especially the orbital region, but also the temporal region, with important improvement in dorsal decubitus and followed by two vomiting episodes. A cranial tomography was requested and revealed the presence of an acute left frontotemporoparietal subdural hematoma. A conservative treatment with analgesics, dexamethasone and hydantoin was indicated. After 17 days, the patient had intense headache, followed by dormancy and paresis of right upper limb and speech and behavior disorders. The hematoma was surgically drained. The patient evolved well and without sequelae. CONCLUSIONS: Headache is the most frequent complication after spinal anesthesia and it is considered of benign evolution. In many cases however, it leads to the late or absent diagnosis of potentially fatal conditions, like subdural hematoma. This case describes a rare case of an acute subdural hematoma following spinal anesthesia with fine-gauge needle in a patient without risk factors for bleeding